Snowball Throwing Learning Model (STLM): Is It Effective to Improve Students' Cognitive Abilities and Learning Motivation in History Learning at the High School Level - Khusna, Nur Isroatul; Rhodinia, Shella; Zahroh, Luluk ‘Atirotu (IJTIMAIYA: Journal of Social Science and Teaching, 2025)
History learning, especially at the high school level, requires innovation because it often faces obstacles in the form of extensive material that can leave students less motivated and make it challenging to achieve optimal cognitive performance. This study aims to test the effectiveness of the Snowball Throwing Learning Model (STLM) in improving students' cognitive ability and learning motivation in Dutch colonial materials in grade XI of SMAN 1 Kauman. The research used a quasi-experimental design with a quantitative approach, involving an experimental group and a control group consisting of 30 students each. Data were collected via learning outcome tests and motivation questionnaires and analyzed using t-tests and MANOVA. The results showed a significance value (2-tailed) of 0.000, which is smaller than 0.05, indicating that STLM has a significant effect on students' motivation and cognitive abilities. This model encourages students to actively engage in cooperative activities, exchange information, and develop critical thinking skills through the dynamic process of creating and discussing questions. In addition, STLM enhances classroom interaction, students' creativity, and their understanding of historical concepts. These findings suggest that STLM is effectively applied in history learning at the high school level and has the potential to be adopted more widely to support active, collaborative, and meaningful learning.